BEM-ESTAR FARMACÊUTICO, HEALTH MADE EASY. (CIPEEX, 2025)
The project “Bem-estar Farmacêutico” is a medicine delivery system where users search for the medicine they need through the app, find a pharmacy linked to the app that has the medication available, and make the purchase. The initiative, categorized as a proposed solution, offers a medication delivery service connected to pharmacies, providing convenience for users who need medicine without the need for physical travel. This solution is designed to facilitate safe and practical access to medications, addressing the needs of the healthcare sector. The primary focus is to serve people with mobility issues, caregivers of the elderly, and those who require regular medication, offering an efficient and accessible way to acquire these products, though it proves useful for any person in any condition. The app allows users to search for medications, compare prices and delivery times, and ensures the security of packaging and adherence to privacy standards. The main objective is to democratize access to medications, improving users’ quality of life by offering a fast and reliable delivery service. Additionally, the proposal benefits not only the users but also improves pharmacy delivery conditions, acting as a support channel in delicate situations and promoting general well-being.
Keywords: medications; accessibility; pharmacies; delivery